ARTIFICIAL INTELLIGENCE IN ACADEMIA: OPPORTUNITY OR CHALLENGE? - L.H. Grigoryan; M. V. Badalyan; A.Z. Grigoryan (Aktualʹnì Problemi Rozvitku Ekonomìki Regìonu)
In recent years, the rapid advancement of Artificial Intelligence (AI) has had a profound and transformative impact across a wide range of sectors, including education and scientific research. As the primary environment for the generation, exchange, and preservation of knowledge, academia finds itself at the forefront of this technological shift. AI presents a dual reality for academic institutions: it brings forward unprecedented opportunities for innovation and efficiency, while simultaneously introducing complex ethical, pedagogical, and operational challenges.